Management of refractory breathlessness with morphine in patients with chronic obstructive pulmonary disease. Issue 9 (September 2015) - Smallwood, N.; Le, B.; Currow, D.; Irving, L.; Philip, J.
Abstract Chronic obstructive pulmonary disease (COPD) is a progressive, incurable illness, which leads to significant morbidity over long periods of time and mortality. Treatment aims to reduce symptoms, improve exercise capacity and quality of life, reduce exacerbations, slow disease progression and reduce mortality. However, breathlessness is common in patients with advanced COPD and remains undertreated. As all reversible causes of breathlessness are being optimally managed, consideration should be given to specific non‐pharmacological and pharmacological treatment strategies for breathlessness. Low dose morphine has been shown to reduce safely and effectively breathlessness in patients with severe COPD and refractory dyspnoea. However, despite numerous guidelines recommending opioids in this clinical setting, many barriers limit their uptake by clinicians. Integration of palliative care earlier in the disease course can help to improve symptom control for people with severe COPD and refractory breathlessness. A multidisciplinary approach involving both respiratory and palliative care teams offers a new model of care for these patients.